Assets Structure Of Chandigarh Transport Undertaking - Goyal, Munish (Gyan Management Journal, 2020)
Assets are the  resources owned by an undertaking. They  represent ownership value which  can be  converted into cash. Tangible assets include fixed assets and current assets. Fixed assets have a physical  form and are typically bought for production and supply of goods and services and provide a long term  gain to the concern. They are not essentially fixed in all senses of word. Moreover they lose value as they  are used. Current assets are meant to be converted into cash and are not depreciated. They basically  indicate healthy liquidity position of the undertaking. Chandigarh Transport Undertaking (CTU) being  a public transport unit of Chandigarh has to invest a large amount of funds in the fixed assets and have  to hold a huge inventory as a part of current assets.
Keywords: Fixed assets; current assets; investment; growth rate; trend.